Regional Variability in Longitudinal Strain Across Vendors in Patients With Cardiomyopathy Due to Increased Left Ventricular Wall Thickness. (August 2019) - Sperry, Brett W.; Sato, Kimi; Phelan, Dermot; Grimm, Richard; Desai, Milind Y.; Hanna, Mazen; Jaber, Wael A.; Popović, Zoran B
Abstract : Background: Cardiomyopathies with increased left ventricular wall thickness such as cardiac amyloidosis, septal hypertrophic cardiomyopathy (HCM), and apical HCM exhibit characteristic regional longitudinal strain (LS) patterns. However, between-vendor agreement of segmental and regional LS has not been tested in these diseases. We sought to assess LS values among vendors in specific cardiomyopathies that exhibit regional strain variation: cardiac amyloidosis, septal HCM, and apical HCM. Methods: This was a prospective, cross-sectional study of 69 patients (18 amyloidosis, 30 septal HCM, 6 apical HCM, and 15 controls) who underwent clinically indicated outpatient echocardiography at the Cleveland Clinic. Peak systolic segmental, regional (basal, mid, and apical), and global LS were evaluated using GE (EchoPAC), Siemens (Velocity Vector Imaging), and Phillips (QLab) systems in the same imaging session. Between-vendor, differences were analyzed using correlation coefficients, Bland Altman plots, and a mixed model. Results: Global LS was highly correlated among the 3 software packages and most abnormal in patients with amyloidosis ( P <0.001). Regional LS analysis demonstrated that QLab software tended to produce more negative LS values, driven by differences in apical strains. EchoPAC had the greatest ability to discriminate patients with amyloidosis using regional strain values (area under the curve, 0.932) as compared with Velocity Vector Imaging and QLab ( P <0.001). Conclusions: Global and regional variations in LS exist between-vendors in patients with cardiomyopathies with increased left ventricular wall thickness (amyloidosis, septal HCM, and apical HCM). It is important to be aware of these differences for diagnosis, prognosis, and serial examinations in these conditions.